Antioxidant Activity of Peel Fraction of Seven Pomegranate (Ripe and Unripe) Varieties Grown in Iran - Mirmohammadi, Mehrosadate; Jamshidi, Majideh (Asian Journal of Chemistry, 2010)
Antioxidant capacity and total phenolic compounds of peel fraction of seven pomegranate varieties grown in Iran were determined. The effect of maturation on antioxidant activity was also determined. The results showed that Pust Ghermeze Shirin (sweet taste with red peel) had the highest antioxidant value among all varieties and followed by Pust Sefeede Shirin (sweet taste with white peel), Yazdi (sub acid taste with pink peel), Pust Ghermeze Torsh (sour taste with red peel), Pust Sefeede Torsh (sour taste with white peel), Malas (sub acid taste) and Makhmali (sub acid taste with velvet peel). Maturation of pomegranate increased the antioxidant capacity.